The effectiveness of the bullwhip effect in the Drag-flick in field hockey - C. López de Subijana; R. De Antonio; D. Juarez; E. Navarro (Asociación Española de Ciencias del Deporte, 2010)
The penalty corner is one of the most important goal plays in field hockey. The drag-flick is more efficient than other techniques when playing a penalty corner. The aims of this study were to describe the kinematics of international field hockey players during the drag-flick and to analyse gender differences. Thirteen participants, one male drag-flicker, six males and six females participated in the study. VICON optoelectronic system measured the kinematic parameters from the drag-flick with six cameras sampling at 250 Hz. Twenty trials were captured from each subject. Ball velocity at release, hips maximum angular velocity, stick minimum and maximum angular velocities were higher (p<0.01) in the drag-flicker than in both gender groups. Comparing with the drag-flicker we have found the cues of the skill, being necessary a whipping effect of the stick before an explosive movement of hips, shoulders and a maximum acceleration of the stick. Key Words: Biomechanics, drag-flick, field hockey, kinematics.